DETERMINANTS AND MITIGATION FACTORS OF TAX EVASION : INDONESIA EVIDENCE - Yolisia Framita Agus; Indah Umiyati; Asep Kurniawan (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2019)
This study aims to determine the effect of justice, system, understanding, tax rates and sanctions on tax evasion. The method used in this study is descriptive quantitative by using primary data. The technique of collecting data with a questionnaire distributed to corporate taxpayers registered at Pratama KPP with a sample of 110 respondents. Data analysis in this study is multiple regression with SPSS version 22 program. The results of this study indicate that understanding taxation affects tax evasion. While justice, system, tax rates and sanctions have no effect on tax evasion.